Spin relaxation in semiconductor nanostructures - Hachiya, Marco Antonio de Oliveira (2013)
In the research field of spintronics, it is essential to have a deep understanding of the relaxation mechanisms of the spin degree of freedom. To this end, we study the spin relaxation in semiconductor nanostructures with spin-orbit interaction. First we analyze the spin decay and dephasing in graphene quantum dots within the framework of the Bloch-Redfield theory. We consider a gate-tunable circular graphene quantum dot where the intrinsic and Rashba spin-orbit interactions are operative. We derive an effective Hamiltonian via the Schrieffer-Wolff transformation describing the coupling of the electron spin to potential fluctuations generated by the lattice vibrations. The spin relaxation occurs with energy relaxation provided by the electron-phonon coupling and the spin-flip transition assisted by spin-orbit interactions. We predict a minimum of the spin relaxation time T1 as a function of the external magnetic field Bext caused by the Rashba spin-orbit coupling-induced anticrossing of opposite spin states. By constrast, the intrinsic spin-orbit interaction leads to monotonic behavior of T1 with Bext due to direct spin-phonon coupling. We also demonstrate that the spin decoherence time T2 = 2T1 in graphene is dominated by relaxation processes up to leading order in the spin-orbit interaction and the electron-phonon coupling mechanisms. Secondly, we develop a numerical model to account for the D´yakonov-Perel spin relaxation mechanism in multisubband quantum wires. We consider the elastic spin-conserving scattering events in the time-evolution operator and then evaluate the time-dependent expectation value of the spin operators. After averaging these results over an ensemble, we can extract the spin relaxation time as a function of Bext. We observe a non-monotonic behavior for the spin relaxation time with Bext aligned perpendicularly to the quantum wire. This effect is called ballistic spin resonance. In our model, the ballistic spin resonance occurs near the subband anticrossing induced by the subband-spin mixing spin-orbit interaction term. In systems with weak spin-orbit coupling strenghts, no spin resonance is observed when Bext is parallel to the channel. Nevertheless, we also predict the emergence of anomalous resonances plateaus in systems with strong spin-orbit couplings even when Bext is aligned with the quantum wire. Finally, we predict the emergence of a robust spin-density helical crossed pattern in two-dimensional electron gas with Rashba α and Dresselhaus β spin-orbit couplings. This pattern arises in a quantum well with two occupied subbands when the spin-orbit coupling strenghts are tuned to have equal absolute strengths but opposite signs, e.g., α1 = +β1 e α2 = −β2 for the first v = 1 and second v = 2 subbands. We named this novel pattern as crossed persistent spin helices. We analyze the spin-charge coupled diffusion equations in order to investigate the lifetime of the crossed persistent spin helices and the feasibility of probing the crossed persistent spin helix mode. We also study the inteband spin-orbit interaction effects on the crossed persistent spin helices, energy anticrossings and spin textures induced by the interband spin-orbit coupling